Efficacy of pimecrolimus 1 % cream in the long term management of atopic hand dermatitis: a double-blind RCT - Bauer, Andrea; Matterne, Uwe; Diepgen, Thomas L. (Journal der Deutschen Dermatologischen Gesellschaft, 2012)
Background: Efficacy and steroid sparing effects of pimecrolimus 1 % cream in atopic dermatitis have been shown recently, but there is no data on efficacy in long term management of atopic hand dermatitis. This study aims to investigate the efficacy of pimecrolimus 1 % cream as maintenance therapy in patients suffering from atopic hand dermatitis. Patients and Methods: A double-blind vehicle controlled study in 40 adult patients with atopic hand dermatitis (IGA < 3) comparing the efficacy of twice daily application of pimecrolimus 1 % cream given as maintenance treatment versus vehicle over a 8 week period after clinical response (IGA < 2) to a 1-3 week pre-treatment with mometasone fuorate 0.1 % was performed. Primary endpoint was the time to relapse (IGA > 3). Results: Thirty-six out of 40 patients were randomised to receive either pimecrolimus 1 % (P) or vehicle cream (V). The number of patients with stable remission in patients randomised to pimecrolimus (53.8 %) and vehicle (43.8 %) did not achieve statistical significance between the groups (p = 0.41). Subgroup analysis of patients with initially moderate dermatitis (IGA = 3, n = 20) showed a trend towards a better outcome for the pimecrolimus group (stable remission P = 81.8 % versus V = 55.6 %) (p = 0.244). Conclusions: Pimecrolimus 1 % cream twice daily was not superior to vehicle in the sequential maintenance therapy of atopic hand dermatitis, but efficacy in moderate forms should be investigated in further studies.